Prospective of Essential Oils of the Genus Mentha as Biopesticides: A Review - Singh, Pooja; Pandey, Abhay K. (Frontiers in Plant Science, 2018)
Mentha is a genus from the family lamiaceae, whose essential oils has long been used in various forms such as in the management of plant pathogens and insect pests, in traditional medicine as well as in culinary, cosmetics etc. Its major chemical components such as menthol, carvone have now been successfully commercialized in industry as antimicrobials/insecticidal agents. Current review focuses on chemical composition of essential oils of some Mentha species of different geographical regions with their insecticidal (repellent, antifeedent, ovicidal etc.) and antimicrobial efficacy. Reports of researchers on the chemical analysis of the essential oils of Mentha species revealed that most of the oils being rich in pulegone, menthon, menthol, carvone, 1, 8-cineole, limonene, β-caryophyllene Reviewed literature revealed that, essential oils from different Mentha species possess potential antimicrobial activity against plant pathogens and have insecticidal activity against stored product insects. Thus, these antimicrobial and insecticidal properties of essential oils of Mentha species offer the prospect of using them as natural pesticides with a commercial value, having social acceptance due to its sustainability and being environment friendly.